2007
DOI: 10.1353/dem.2007.0026
|View full text |Cite
|
Sign up to set email alerts
|

Chronic conditions and the decline in late-life disability

Abstract: Using data from the 1997-2004 National Health Interview Survey (NHIS), we examine the role of chronic conditions in recent declines in late-life disability prevalence. Building upon prior studies, we decompose disability declines into changes in the prevalence of chronic conditions and in the risk of disability given a condition. In doing so, we extend Kitigawa's (1955) classical decomposition technique to take advantage of the annual data points in the NHIS. Then we use respondents' reports of conditions caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
113
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 37 publications
12
113
0
Order By: Relevance
“…Like prior studies, we found an important role for shifts in the educational distribution of the older population (Freedman & Martin, 1999;Waidmann & Liu, 2000) and for late-life vision improvements (Freedman et al, 2007). The latter we found related not only to declines in the prevalence of ADL limitations but also to reductions in onset and increases in recovery.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Like prior studies, we found an important role for shifts in the educational distribution of the older population (Freedman & Martin, 1999;Waidmann & Liu, 2000) and for late-life vision improvements (Freedman et al, 2007). The latter we found related not only to declines in the prevalence of ADL limitations but also to reductions in onset and increases in recovery.…”
Section: Discussionsupporting
confidence: 84%
“…Substantial increases in the educational attainment of the older U.S. population occurred during the 1980s and 1990s, and this change has been identified as a major contributor to declines in late-life disability prevalence. However, Freedman and Martin (1999) predicted that this education bonus might not continue into the future, and more recent evidence suggests that the benefits of increased educational attainment may have leveled off (Freedman, Schoeni, Martin, and Cornman, 2007).…”
Section: Educationmentioning
confidence: 99%
“…Crimmins 2004, Crimmins andBeltran-Sanchez 2010). Generally, it appears that while the prevalence of chronic conditions among the elderly has increased, the extent to which these conditions lead to disability has declined (Freedman et al 2007). Recent evidence also shows that the trend in the increase in healthy life expectancy may have recently started to reverse, at least in the US.…”
Section: The Debate On Healthy Life Expectancy: Demographic and Economentioning
confidence: 99%
“…Reductions in cardiac risk factors, such as uncontrolled hypertension, and innovations in pharmacological and surgical therapies may have contributed to the declines in discharge rates shown here, and to declines in disability and mortality from heart disease noted elsewhere. 13 Increasing ambulatory care visit rates for diabetes are consistent with improved diagnosis and health-related outcomes, including control of glucose and blood pressure levels. 14 Mushrooming levels of treatment for arthritis in ambulatory and hospital settings may reflect both the challenge of effective therapy for some conditions, such as low-back pain, and diffusion of effective technologies, such as knee or hip replacements.…”
mentioning
confidence: 99%